A Self-nanoemulsifying Drug Delivery System for Poorly Water Soluble Tolbutamide: Development, Optimization and Pharmacodynamic Studies - Pandita, Deepti; Kumari, Neelam; Lather, Viney (Pharmaceutical Nanotechnology, 2017)
Background: Self-nanoemulsifying drug delivery system (SNEDDS) has immense potential in oral bioavailability enhancement of lipophilic drugs. Objective: This investigation involves the development of thermodynamically stable and dilutable SNEDDS for tolbutamide, for achieving higher water solubility and enhanced dissolution rate which in turn improves its oral bioavailability. Method: Preliminary solubility studies were carried out and pseudo-ternary phase diagrams were plotted for selection of best ratio of surfactant and co-surfactant. The drug loaded SNEDDS were prepared, characterized w.r.t. refractive index, viscocity, globule size, zeta potential, and TEM, and converted into solid self-nanoemulsifying granules (SSNEGs). These were further characterized and their antidiabetic efficacy in male Wistar rats was evaluated. Results: Solubility studies suggested the suitability of oleic acid as lipid phase; Tween 20 and PEG 400 as optimal surfactant and co-surfactant, respectively for formulation of SNEDDS formulations. The optimal SNEDDS formulation having mean globule diameter, viscosity, polydispersity 58.55 ± 0.2 nm, 26.18 ± 0.2 cps, 0.277 respectively, and infinite dilution capability displayed a highly significant increase in dissolution rate within 5 h compared to pure drug suspension. The SSNEGs showed 1.54 fold increase in drug dissolution rate compared to pure drug. Stability studies revealed no significant change in morphology and globule size. Anti-hyperglycemic activity of tolbutamide loaded SSNEGs in rats showed a significant reduction in elevated blood glucose level with absence of ketone and glucose in urine. Conclusion: The present study demonstrates a successful development of SNEDDS formulation with an overall potential of bioavailability enhancement for tolbutamide, a BCS-II drug.
Keywords: self-nanoemulsifying drug delivery system